A retrospective analysis of a commercially available platelet‐rich plasma kit during clinical use. Issue 12 (12th April 2021) - Prysak, Meredith H.; Kyriakides, Christopher P.; Zukofsky, Tyler A.; Reutter, Stefan E.; Cheng, Jennifer; Lutz, Gregory E.
Abstract: Introduction: Point‐of‐care analyses of platelet‐rich plasma (PRP) are not routine in the orthopedic regenerative medicine field. Therefore, many physicians rely on the manufacturer's reported content for commercial preparation kits. This contributes to a knowledge gap between injectate content and patient outcome. Objective: To assess whether the EmCyte PurePRP II 60‐mL preparation kit returns PRP content that meets the manufacturer's expectations when used during routine clinical care for a heterogenous patient population, and to determine whether a change in PRP yield volume affects injectate content. Protocol A (exclusion of granulocytes and low hematocrit) and Protocol B (inclusion of granulocytes and higher hematocrit) were evaluated. Design: Retrospective review. Setting: Private practice. Participants: One hundred five patients (118 preparations) treated for orthopedic conditions over an 8‐month period via PRP injection. Thirteen patients had two independently made preparations on different treatment days that qualified for analysis. Interventions: Not applicable. Main Outcome Measures: Complete blood count (absolute counts and calculated fold enrichment from baseline of platelets, white blood cells, red blood cells, granulocytes, lymphocytes, monocytes; and hematocrit levels). Confounding variables included age, gender, and preparation yield volume. Results: During routine clinical use, the cellular content of both Protocols A and B met or exceeded the manufacturer's expectations of platelet enrichment and granulocyte inclusion or exclusion. Hematocrit values were slightly higher than anticipated from Protocol A preparations. The modification of yield volume from 7 to 4 mL led to a significant difference in platelet enrichment without affecting absolute cell counts (2.88; 95% confidence interval [CI] 1, 4.76; P = .003). Both gender and age moderately affected the level of platelet enrichment from baseline but did not significantly affect absolute platelet counts. Conclusion: In the absence of widespread characterization, confirming the variation in commercial PRP kits during clinical use is crucial.